Masalah Mafia Peradilan dan Penanggulangannya - artidjo alkostar (Jurnal Hukum IUS QUIA IUSTUM, 2002)
In criminology perspactives, there many factors can be identified as the stimulant condition the emerge of melajudicial action. One oftheis making relation between who uphold the lawandthe party involved. Ideally, the twoparties inrelation of case mustbe professional but in reality the pattem emergeis transactionai The serious implication of suchrelation pattern cause the negative impacts forthe aspects of havingnation andhavingcountty. Logically by the glow of melapractice on judicial, sotheef for to prevention must beputinto actionim mediately. This prevention is beap proached by not only law enforce-mentaspect butit must bespreaded widelytill anykinds of controllingfrom thegovern mentboard, and itmakes mote society advocates who those suffered by the law enforce ment.